Fordulóponton a magyar területfejlesztési politika, avagy szem elől veszítjük-e a francia mintát? - Barta, Györgyi (Tér és Társadalom, 1992)
In Hungary, the elaboration of regional development policy started in the 1960s. The 30 years of regional development policy are evaluated in the most extreme ways; There are some who find this activity fundamentally successful, as has it reached its most important goal, the moderation of regional-aconomic-social differences. Others question whether regional development policy had any influence whatsoever on the regional changes of the socio-economic processes. However, neither the affirmative nor the doubting opinions deny that the regional development policy was the product of the socialist economic system between 1961 and 1989, and that this system was characterized by both the general socialist and the specific Hungarian features. Consequently, its success and failures can be explained exactly with these characteristics. When studying the history of French regional development policy, strange similarities can be found between the French and the Hungarian intentions, and these similarities are not accidental at all. The French regional development policy served as an example for the Hungarian experts already in the very beginning. France, which is far more centralized than the other West-European countries, can be a pattern, and a kind of „reference country" for the Hungary in transition these days. In France, regional development policy became an integrated part of the government policy, because the French accept quite well the idea of caring about underdeveloped regions, and as the conflict between the overdeveloped capital city and the rest of the country has always been and still is a fundamental issue. However, highlighting the above similarities in development can be interesting in itself, just by showing the different results brought about by similar efforts in the two countries with different political systems and levels of economic development. The parallel tendencies, that could be detected in France until the mid-1970s, and in Hungary until the end of the 1980s, are over now. The new economic conditions weakened the French regional development policy. DATAR worded and announced its new economic development policy during the Tast one or two years as an answer to the challenges of new economic, social and political conditions. The Hungarian regional development policy has also weakened, its ideological foundations are shaken, the efforts to ease social and economic inequalities have become extremely timely and, at the same time, outdated, and the financial resources of regional development are more limited than ever. Does Hungarian regional development policy pay any attention to the French example, which fights for preserving its positive traditions, or will the spatial influences of spontaneous market proecesses gain ground? In my opinion, this is a good enough reason to learn more about the present French regional policy. The beginnings of the French regional development policy can be dated back to the 1950s. In the middle of the 20th century, two basic spatial conflicts became extremely strong in France: one of them was the conflict between the overgrown capital city, Paris, and the rest of the country (one-sixth of the population in France was concentrated in Seine and Oise counties, while only one-twentieth had lived in this region a hundred years before; in the first half of the century, the number of industrial employees increased by 50% in the Paris agglomeration, while the national average was only 3 %; in the 1950s, Paris concentrated 70% of bank employees, 60% of business turnover, and 40% of higher education) and the other conflict could be identified among the rural regions (East of the the Havre-Marseille axis, the living standards were twice or three times higher than in the regions West of the axis). It was the time when the first general regional development policy was worded, and its classical elements – decentralized industrial development, modernization of agriculture, development of tourism and infrastructure, decentralization of culture – were applied by all those countries where regional development was taken into consideration. The necessity of the development of underdeveloped regions was codified by law in 1955-56, and this was extended with two more regulations: the adminsitrative prevention of the further growth of the Paris region (the foundation of industrial enterprises exceeding a certain size had to be licensed in advance, permissions to construct new offices and scientific institutions would not be granted for 3 years), and the establishment of an economic and regional development fund (Fonds de Dévéloppement Économique et Social) to cover the relocation costs of industries and the costs of establishing new industries in the regions to be developed. This was the time when the comprehensive development program of the 22 regions was elaborated. This regional development project was not too very successful. The companies relocated from Paris tried to settle down in a 200-km radius from the capital city. The efforts to decentralize the scientific and educational institutions ended up in complete failure. The Hungarian regional develoment project applied the above measures only in part and at a later date, but did not learn anything of its failures. The decentralization of industry and the modernization of agriculture were accepted, but the infrastructural development was neglected, not to speak about the decentralization of culture. The administrative economic regulations which aimed to stop the development of Budapest were extended, in addition to increasing the severity of regulations on settling down in Budapest. The Regional Development Fund was created fairly late, only in 1971, and it was an insignificant amount and gave about 1% of the industrial investments of the time, and oriented only about 4-5 % of all the investments. After some years, the Regional Development fund ceased to exist. Until the mid-1970s, VÁTI (Scientific Institute for Urban Development) elaborated development plans for the counties, which were similar to the French development projects. The French were lucky to draw the conclusions on the inefficiency of the means and methods of regional development policy already in the period of prosperity. In the mid-1960s, there was a chance to initiate new, global regional development activities. The French were aware that no regional development project could be succesful without overall decentralization. Decentralization of power is the most delicate and most difficult issue, and its success could be celebrated by the French only several years after the implementation. Under Hungarian conditions, no decentralization could take place as it contradicted the rules and principles of the socialist regime. Though the role of county councils increased from the 1970s, they remained primarily the executors of central decisions, and had very little field for independant activities. The new economic mechanism, which granted rather big independence to the companies, did not touch the institutional structure. In the period of economic prosperity, in the 1960s and 1970s, production was spread all over the country, but the management and control of production remained centralized. „Divison industry" became dominant in large zones and counties, but it had no roots, and did not generate further development in the neighbourhood. Consequently, these industries s ion, got into an uncertain position due to unfavourable economic conditions. It is not accidental that this industrialization project was called colonialization. Though the population increase and the effective growth of the economy could be stopped in the administrative arca of Budapest, the agglomeration of Budapest developed dynamically, and its population density increased rapidly.